Dahulu Kampung Ganja Sekarang Kampung Wisata; Pemberdayaan Ekonomi Masyarakat Muslim Aceh Gayo - Sukri, Sukri; Adrianda, Irsan; Hidayat, Mansur (BINA' AL-UMMAH, 2020)
This article would like to discuss institutional efforts and strategies in empowering community, to change  the culture of the Moslem community;  those that are unproductive and even destructive, into a productive agricultural economy, eliminating cultures that are rooted in community traditions, instill a culture of agriculture that new, and change the environment by integrating the agricultural / plantation environment combined with the tourism environment. The changes that were successfully realized then had broad implications, especially in improving the economic welfare of the community.Community empowerment is an effort to realize individuals and social changes. It is chosen as a solution to the social problems faced by communities; especially the problem of poverty. Poverty as a social problem should be solved, for empirically it opten carries other implications, such as criminality, violation of norms and even violations of laws. Agusen Village, located at the foot of the Leuser Gayo Lues mountains, was formerly known as a cannabis village, but now it has become a village of tourisme in Gayo Aceh. Tourism-based economic activities in this village are exist in the form of; providing tourism objects and facilities, local culinary, home stay rents as a tourist lodging facilities, and various other economic activities in the service of tourists who visit this village . The existence of this village (Agusen) which has become a tourist village, has implications to the economic development of rural communities. The economic activities of these rural communities are not only dependent on subbsistence agricultural economic activities, but they already have the ability to develop economic activities into the tourism sector, which has impacts on increasing economic prosperity. The collective capacity of the community in managing tourism economic activities is manifested through systematic efforts made by local governments (sub-districts and districts government); by providing a series of informal education activities designed to foster the communities’ awareness, develop their capacity and strengthen traditional institutions as institutional ties that foster the communities’ togetherness for simultantly developing. Agusen communities and village. Efforts to raise awareness about the existing potential are carried out with a series of extension activities. While technical capacity and capability in managing tourism-based economic activities is carried out by providing either managerial and technical training.